Task-based Activities in TEFL - Fachrurrazy Fachrurrazy (TEFLIN Journal: A publication on the teaching and learning of English, 2000)
Abstract This article presents a discussion of task-based approach in Communicative Language Teaching. A task is a classroom activity inÃÂvolving learners interaction in which the main attention is on the meanÃÂing more than on the form of the target language. This approach may be applicable to TEFL in Indonesian context.